PELATIHAN PENGOLAHAN “PAYA BITES”, CEMILAN SEHAT BERBAHAN PEPAYA, BAGI ANGGOTA FKIF UNNES - Na’im, Muhammad Rizqu Zidan; Aulia, Akhisna Citra; Mariska, Mela; Kamilia, Habibah Nurul; Husna, Alifah Fiani Salwa (Universitas Bunda Mulia, 2024)
Papaya is a seasonal fruit that is rich in water content and has a relatively short shelf life. Nowadays, people's interest in consuming fruit directly after it is ripe is relatively low because some of them don't like fruit. For this reason, it is necessary to innovate fruit-based products, as an effort to overcome the problem of lack of fruit consumption. This article discusses